Metodologia do ensino da Filosofia no ensino médio, na perspectiva da maiêutica Socrática - Melo, Francisco Cleano Lima (2019)
The present study has as objective to present a methodological proposal of teaching philosophy in high school with reference to Socratic maieutics. For this undertaking, the reading and analysis of texts by Xenophon (Socrates’ Sayings and Memo rable Achievements and Socrates' Apology) Apology), Aristophanes (The and Plato (Defense of which present us with a "portrait" of Socrates, considering that the latter left nothing to do with writing. In all of them we try to highlight the most important features of Socrates' life and activity. Subsequently material and methods of the activities related to the focal group were presented, emphasizing the use of Socratic maieutics, also the latter object of due appreciation. Research is also based on the sharing of group ideas, dialogue, reading, questions, questionnaires and experiences reports. In this sense, at the end of this philosophical enterprise, the results and the discussions of the research were presented, having as presuppositions, the bibliographical reference and the methodology based on the maieutic. By means of the dialogical attitude realized in the focal group it was possible to perceive the contributions of the Socratic philosophy to the high school in the present time. The questi oning was shown as a possibility to think and reflect critically, becoming a path to conceptual construction through dialogue and reading. At the conclusion of the research, the contribution of the Socratic method to the teaching of philosophy in High Scho ol is highlighted.